Serum choline, leptin and interleukin-6 levels in fibromyalgia syndrome-induced pain: a case–control study - Elif Baris; Izel Topaloglu; Elif Akalin; Emre Hamurtekin; Seray Kabaran; Ayse Gelal; Reyhan Ucku; Mualla Aylin Arici (BMC Musculoskeletal Disorders)
Abstract Background Fibromyalgia Syndrome (FMS) predominantly affects middle-aged women, characterized by musculoskeletal pain, fatigue, and cognitive issues. Choline, an endogenous molecule, may influence FMS due to its analgesic and anti-inflammatory properties. This study compared choline, leptin, and interleukin-6 (IL-6) levels in FMS patients and controls and examining their association with pain severity. Methods Volunteers with FMS were clinically diagnosed at a Physical Medicine and Rehabilitation Department. The control group included pain-free volunteers. Pain severity was gauged using a numeric scale, dietary choline intake through a questionnaire. Serum choline, leptin and (interleukin)IL-6 levels were measured from fasting blood samples of volunteers with enzyme-linked immunosorbent assays (ELISA). Results All FMS patients (n = 38) and healthy volunteers (n = 38) were female. Pain score in patients with FMS was 7.6 ± 0.2. Dietary choline intake was lower in patients with FMS than the controls (p = 0.036). Serum choline and leptin levels were lower in the FMS group compared to control (p = 0.03). Serum IL-6 levels were higher in the FMS group than in the control (p < 0.001). There was weak positive correlation between IL-6 levels and pain scores and there were no correlation between leptin levels and pain scores in FMS. Conclusions This research highlights FMS's complex nature, involving neurochemical, immunological, and nutritional factors. It suggests the significance of choline's anti-inflammatory effect, leptin's metabolic function, and IL-6's role in FMS pathology. The results suggest that reduced dietary choline might influence serum choline, leptin, and IL-6 levels, potentially impacting FMS-related pain. This points to the potential of supplementary choline intake in FMS management. Trial registration Not applicable (Non-interventional study).